The new and the old: littoral tanaidomorph Tanaidacea (Crustacea: Peracarida) from the Andaman Islands, Indian Ocean - Bamber, Roger N; Chatterjee, Tapas (Zootaxa, 2010)
Recent collections of tanaidaceans from intertidal macroalgae on the shores of the Andaman Islands have revealed both new taxa to science and new material of a species which had previously been inadequately described. The present paper gives a redescription of the leptocheliid Konarus crassicornis, discussing its close similarity to the generotype, K. cheirus, and describes two new species, one of the tanaid genus Zeuxo, showing similarities to Z. (Parazeuxo) kurilensis and representing the first anatanaid to be recorded from the region, and one paratanaid of a new genus, Triparatanais, distinguished from other paratanaids in having only three longer articles in the antennule.